2011
DOI: 10.1007/s13197-011-0231-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of drying process parameters for cauliflower drying

Abstract: The different sizes (3, 4 and 5 cm) of hybrid variety of cauliflower (variety no. 71) were dehydrated in thin layer at three temperatures of 55, 60 and 65°C with velocities of 40, 50 and 60 m/min. Dehydrated samples were analyzed for vitamin C, rehydration ratio and browning. Statistical analysis indicated that drying time was dependent on initial size of cauliflower, drying air temperature and velocity, but rehydration ratio was significantly affected by the combined effect of temperature and airflow velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 24 publications
8
33
0
Order By: Relevance
“…This was because of a larger driving force for heat transfer at 70°C as compared with at lower temperatures. A similar trend was also reported by other researchers (Akpinar et al, 2006;Sacilik, 2007;Pin et al, 2009;Jaloszynski et al, 2009;Arslan and Musa Özcan, 2010;Gupta et al, 2013;Arabi et al, 2016). from inside the root was transferred to the surface.…”
Section: Chemical Analysissupporting
confidence: 89%
“…This was because of a larger driving force for heat transfer at 70°C as compared with at lower temperatures. A similar trend was also reported by other researchers (Akpinar et al, 2006;Sacilik, 2007;Pin et al, 2009;Jaloszynski et al, 2009;Arslan and Musa Özcan, 2010;Gupta et al, 2013;Arabi et al, 2016). from inside the root was transferred to the surface.…”
Section: Chemical Analysissupporting
confidence: 89%
“…It is the most sensitive and destructed when a commodity is exposed to adverse handling and storage conditions (Lee and Kader 2000). Vitamin C stability in fruits and vegetables was studied during different methods of drying (Goula and Adamopoulos 2006;Marques et al 2006Marques et al , 2007Gupta et al 2013;Kek et al 2013) and during storage at chilled or around room temperature (Johnston and Hale 2005;Burdurlu et al 2006;Torregrosa et al 2006;Klimczak et al 2007;Majumdar et al 2009;Gonzalez-Molina et al 2012). The loss of vitamin C during storage was considerably lower in freeze dried powder as compared to vacuum, and tunnel dried guava powder (Verma et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…One of the studies, conducted to determine the optimized drying parameters for thin layer drying of cauliflower, showed the drying was effective if drying air temperature was 60.10℃, drying air flow rate was 59.28 m/min, and initial size of the cauliflower was of 3.35 cm [8]. Another study [9] also revealed that the cauliflower samples dried (in thin layer) at 60℃ drying air temperature retained better quality attributes at the end of the 4 months storage.…”
Section: Methodsmentioning
confidence: 99%
“…The cauliflower samples for 4,8,12,16, and 20 cm bed thickness were dried at 60℃ and drying air velocity of 60 m/min. The dryer was started 2 hours earlier the drying runs to get steady state conditions.…”
Section: Dryer Set Up and Drying Conditionsmentioning
confidence: 99%
See 1 more Smart Citation